Archives power : memory, accountability and social justice - Randall C. Jimerson. (Society of American Archivists)
Contents: Introduction : Embracing the power of archives -- Weaving the life of our ancestors -- Documenting American society -- Resisting political power -- Constructing memory -- Serving the public good -- Responding to the call of justice -- Conclusion : Rethinking archival ethics -- Appendix : Memory for justice report.Includes bibliographical references and index.